Visible and Invisible Boundaries of Access: The Case of Private Archives in Turkey (Atlanti +, 2026)
Purpose: Private archives occupy a distinctive position in that they have the capacity to reflect individual lives and actions in an unfiltered and uncensored manner. This study aims to identify and categorise access restrictions applied in private archives by tracing their underlying rationales, and to examine whether the restrictions imposed on personal and family archives are consistent with ethical principles, legal frameworks, and professional standards. Method/Approach: Using a qualitative approach based on document analysis and comparative case studies, the research examines international archival guidelines alongside access practices in five private archives in Turkey to classify restrictions through content analysis. Results: The findings reveal that access restrictions in private archives cluster around three interrelated domains; legal, ethical/privacy-related and operational practices, and that the absence of formal access policies results in inconsistent and opaque implementations. Conclusions/Findings: The study concludes that access restrictions in private archives are multi-layered phenomena and that clearly defined institutional access policies are essential for ensuring transparency, accountability, and alignment with professional and ethical standards.
Keywords: Access restrictions; Privacy; Confidentiality; Private archives; Archival ethics